Surface and deep water variations during MIS 11-15 at IODP Site U1313 in the Mid-Latitude North Atlantic : insights into Mid-Pleistocene rapid climate change - Voelker, Antje H. L. (2015)
AGU Fall Meeting, S. Francisco (USA), 19-14 December 2007